Association between Running Activity and Pronated Foot Posture in East Java Puslatda Athletes - Yani Christina1, Indrayuni Lukitra Wardhani1, Bayu Santoso1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Athlete begins intense exercise at a young age when the musculoskeletal system is still immature, thus it has the potential to cause specific changes in body. A more pronated foot have a greater mobility in both lateral medial plane and vertical plane. Hyperpronated foot allegedly can increase injury risk because it will cause a great moment of force and instability. The research aimed to determine correlation between running activity and pronated foot posture, and to obtain foot posture description of East Java puslatda athletes during running activity in their exercise. Methods: The research employed cross sectional design using 75 athletes, consisting of 43 athletes who run more than 20 km per week and 32 athletes who run less than 20 km per week. The research variables were running activity obtained from questionnaire and foot posture obtained from the Foot Posture Index examination. The study protocol was approved by the ethics committees of Dr. Soetomo Teaching Hospital (Surabaya, Indonesia). Results: The subjects’ demographic data characteristics based on age and exercise duration showed no difference between the two sample groups. On the other hand, the research found a significant difference between age (p = 0.001) and body mass index (p = 0.049). There was no significant correlation between running activity and pronated foot posture, with p = 0.293. Conclusion: The study found that running activity more than 20 km per week had no correlation with pronated foot percentage. Pronated foot posture was commonly found in the sample group with running activity more than 20 km per week, but it was not statistically significant.